2019
DOI: 10.1152/jn.00760.2018
|View full text |Cite
|
Sign up to set email alerts
|

Hand forces and placement are modulated and covary during anticipatory control of bimanual manipulation

Abstract: Dexterous object manipulation relies on the feedforward and feedback control of kinetics (forces) and kinematics (hand shaping and digit placement). Lifting objects with an uneven mass distribution involves the generation of compensatory moments at object lift-off to counter object torques. This is accomplished through the modulation and covariation of digit forces and placement, which has been shown to be a general feature of unimanual manipulation. These feedforward anticipatory processes occur before perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…In healthy adults, compensatory torques are achieved with a combination of force scaling and digit positioning along a spectrum (e.g., [ 18 , 31 , 36 ]; i.e., they use motor equivalence [ 22 ]). Given this flexibility, on trials where the digits are more collinear, the LFs are partitioned during lift-off to a greater extent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In healthy adults, compensatory torques are achieved with a combination of force scaling and digit positioning along a spectrum (e.g., [ 18 , 31 , 36 ]; i.e., they use motor equivalence [ 22 ]). Given this flexibility, on trials where the digits are more collinear, the LFs are partitioned during lift-off to a greater extent.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the reduced magnitude of scaling of digit positions in the USCP groups when the COM was on the side of the thumb, they showed similar covariation of digit placement and forces to controls, which did not support our hypothesis. However, the covariation between digit placement and forces was less compared to healthy adults (typically 0.8 to 0.9) [ 18 , 31 , 36 ], likely reflecting continued development of grasp coordination until adolescence [ 8 ]. Alternatively, it could be due to the considerably lower external torque of the object compared to ones used in adult studies (e.g., [ 20 , 21 ]).…”
Section: Discussionmentioning
confidence: 99%
“…These inconsistent results between robotic assistance in unimanual or bimanual conditions may be connected to the need for studies that elaborate on the mechanisms behind the bilateral training interventions, including the hand dominance, before working on brand new devices for clinical rehabilitation. Addressing this issue, some authors have implemented motor learning paradigms in bimanual environment, using robotic systems to study adaptation due to force field [ 21 , 31 , 32 , 33 ], proposing bimanual versions of the serial reaction time task [ 34 , 35 , 36 , 37 ], or investigating motor acuity by analysing the prehension force during bimanual manipulation [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Force recordings during bimanual manipulation are important to quantitatively analyse the coordination control among limbs, in stroke survivors [ 40 , 41 , 42 ] or healthy and elderly adults [ 39 , 43 , 44 , 45 , 46 ]. Additionally, a recent literature review with meta-analysis showed that patients with stroke have dynamic imparement control of bimanual coordination [ 30 ].…”
Section: Introductionmentioning
confidence: 99%